STUDY OF FACTORS AFFECTING THE LIQUIDITY OF FUTURES CONTRACTS, REGARDING ORDER-BASED CRITERIA - Basirian, Elnaz; Sehatpour, Mohammad Hadi (The journal of contemporary issues in business and government, 2021)
In a liquid market, trades could take place quickly and at a fair price. Considering the importance of liquidity as one of the main indexes of financial markets efficiency, recognizing the factors affecting this phenomenon is a great matter of importance.In this regard, the present study aimed to examine factors affecting the liquidity in Iran’s gold futures market using the data of gold coin future contracts from 2017 to 2018. Being more precise in liquidity measurement due to the concentration on the current market situation, as well as, having a better performance than trading-based criteria in such applications, two order-based criteria of “bid and ask spread” and “the depth of market” were taken into account.Considering the related literature, the most important factors on liquidity such as trade volume, volatility, and price level were identified to investigate their impacts on the liquidity criteria. Subsequently, employing the multivariate linear regression led to the conclusion thatthere is a significant and direct relationship between the volatility of futures contract prices and the depth of market in future contracts on gold coin in Iran Mercantile Exchange (IME) while, the relation between the other factors with the aforementioned criteria are negligible.